Asymptotic work statistics of periodically driven Ising chains. (26th August 2015) - Russomanno, Angelo; Sharma, Shraddha; Dutta, Amit; Santoro, Giuseppe E
Abstract: We study the work statistics of a periodically-driven integrable closed quantum system, addressing in particular the role played by the presence of a quantum critical point. Taking the example of a one-dimensional transverse Ising model in the presence of a spatially homogeneous but periodically time-varying transverse field of frequency, we arrive at the characteristic cumulant generating function G ( u ), which is then used to calculate the work distribution function P ( W ). By applying the Floquet theory we show that, in the infinite time limit, P ( W ) converges, starting from the initial ground state, towards an asymptotic steady state value whose small- W behaviour depends only on the properties of the small-wave-vector modes and on a few important ingredients: the time-averaged value of the transverse field, h 0, the initial transverse field, , and the equilibrium quantum critical point, which we find to generate a sequence of non-equilibrium critical points, with l integer. When, we find a 'universal' edge singularity in P ( W ) at a threshold value of which is entirely determined by . The form of that singularity—Dirac delta derivative or square root—depends on h 0 being or not at a non-equilibrium critical point h * l . On the contrary, when, G ( u ) decays as a power-law for large u, leading to different types of edge singularity at . Generalizing our calculations to the case in which we initialize the system in a finite temperature density matrix, the irreversible entropy generated by the periodic driving is also shown to reach a steady state value in the infinite time limit.